The Apostle of Failure Queer Refusal, the Corinthian Letters, and Paul’s Unflattering Characterization in the Acts of Thecla - Daniel-Hughes, Carly 1974- (2023)
This article examines the Acts of Thecla’s unflattering presentation of the character Paul, as part of the reception of Paul’s Corinthian letters into the second century. Informed by feminist and queer biblical interpretations of the Corinthian exchange, it shows how the Acts of Thecla picks up on tensions over authority with Paul’s teachings on baptism, eschatology, and sexual renunciation in its portrait of Paul. Engaging Jack Halberstam’s The Queer Art of Failure, the article suggests that the Acts of Thecla reads Paul’s letters this way in service of the social critique and queer antagonism that it holds up for its second and third century readers. Where Halberstam claims “queer failure” as resistance to capitalist profit, reproductive futurity, and neoliberal notions of success today, here Thecla’s story is read as a narrative of refusal in its own time. Paul’s muddled encounters with Thecla, steeped in the Corinthian exchange, it concludes, are central to this ancient tale about being, and improbably surviving, outside and at the edges of imperial, civic, and familial frames.
Keywords: Queer Refusal; Baptism; Sexual Renunciation; Corinthian Exchange; Acts of Thecla; Apostle Paul